2022
DOI: 10.3390/pharmacy10040072
|View full text |Cite
|
Sign up to set email alerts
|

Mobile-Based Augmented Reality Application in Pharmacy Schools Implemented in Pharmaceutical Compounding Laboratories: Students’ Benefits and Reception

Abstract: Background: Augmented reality (AR) is a technological approach which combines virtual objects such as text, pictures or videos with physical objects (real-world). The study aimed to design, implement and validate a mobile-based AR application, as a self-paced, interactive, student-centered learning tool be used in the pharmaceutical compounding laboratory course for first year pharmacy students. Method: A mobile-based AR application (Amplified Rx app; HeyPayLess Inc) compatible with iOS and android operating s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Dunleavy et al [76] argue that the most significant limitation with AR technology exists in the stage of development of nascent software and the managerial complexity of the implementation process. In addition, the compatibility with different mobile devices is still an issue for certain AR applications [71], noted also by Nounou et al [45].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Dunleavy et al [76] argue that the most significant limitation with AR technology exists in the stage of development of nascent software and the managerial complexity of the implementation process. In addition, the compatibility with different mobile devices is still an issue for certain AR applications [71], noted also by Nounou et al [45].…”
Section: Discussionmentioning
confidence: 96%
“…Students saw the AR environment as a useful supplementary tool, but they did not wish AR to completely replace traditional laboratory teaching and instruction, despite the fact that the current generation of students is familiar with advanced technologies [3]. In addition, a study by Nounou et al [45] supported the benefit of AR mobile application in a pharmaceutical compounding course. Furthermore, smart glasses and mobile devices have shown the potential in knowledge of human organ systems and physiology [53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Teachers reported that using these technologies has increased student engagement, interaction, cognitive skills and social skills (Alblehai, F.M., 2022; Lamo et al ., 2022; Zholaushievna et al ., 2022). Moreover, students also reported high retention and better learning experience when using AR and VR (Baabdullah et al ., 2022; Nounou et al ., 2022; Monfared et al ., 2022). Thus, it can be clearly inferred that the transformation of learning modalities has benefitted all the main stakeholders of the education industry.…”
Section: Introductionmentioning
confidence: 99%